2001
DOI: 10.1097/00007435-200102000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities for Congenital Syphilis Prevention in an Urban Southeastern Hospital

Abstract: Provider efforts to reduce congenital syphilis in high-risk populations receiving prenatal care should focus on (1) screening patients at the first opportunity, at both the first prenatal visit and during the third trimester (i.e., 28 weeks); (2) performing on-site testing and same-day treatment; (3) providing appropriate treatment to infected women with penicillin allergy; (4) referring sex partners for treatment to prevent reinfection; and (5) screening all pregnant women attending emergency clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 11 publications
1
41
1
7
Order By: Relevance
“…Outros estudos também evidenciaram problemas nas ações para redução da transmissão vertical em gestantes com assistência pré-natal inadequada, como menor acesso aos testes de triagem para sífilis e HIV, [16][17][18][19] maior proporção de casos de sífilis congênita evitáveis por melhor atuação dos prestadores, 20 e maior risco de uso inadequado de medicação antirretroviral na gestação e no parto por gestantes soropositivas para o HIV. 21 A metodologia utilizada, de análise imbricada das informações das gestantes, cartões de pré-natal e profissionais pré-natalistas, revelou concordâncias nos problemas identificados, sinalizando os aspectos da assistência que mais carecem de melhorias.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Outros estudos também evidenciaram problemas nas ações para redução da transmissão vertical em gestantes com assistência pré-natal inadequada, como menor acesso aos testes de triagem para sífilis e HIV, [16][17][18][19] maior proporção de casos de sífilis congênita evitáveis por melhor atuação dos prestadores, 20 e maior risco de uso inadequado de medicação antirretroviral na gestação e no parto por gestantes soropositivas para o HIV. 21 A metodologia utilizada, de análise imbricada das informações das gestantes, cartões de pré-natal e profissionais pré-natalistas, revelou concordâncias nos problemas identificados, sinalizando os aspectos da assistência que mais carecem de melhorias.…”
Section: Discussionunclassified
“…Inadequação na solicitação do segundo VDRL foi também observada em estudo realizado em maternidades de referência no Brasil 26 e em regiões dos EUA com elevada prevalência de sífilis, onde o segundo exame é recomendado como parte da rotina de pré-natal. 16,20,28 A menor solicitação do segundo exame anti-HIV é possivelmente decorrente da implantação recente dessa rotina no município do Rio de Janeiro, ocorrida no mesmo período do início desta pesquisa.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Infected women had lower levels of education; self reported as black or brown in higher proportions; more frequently lived without a partner; had greater exposure to smoking and alcohol; had a greater number of previous pregnancies, births, abortions, and prior negative birth outcomes; had a greater prevalence of HIV infection; and a later initiation of antenatal care. Previous studies had already identified greater social vulnerability among free women with syphilis 42,43 and/or HIV 44 infection.…”
Section: (16%) Strazza Etmentioning
confidence: 97%
“…1,2 Universal prenatal syphilis screening is recommended as one facet in the strategy for the elimination of congenital syphilis, 3 however there is limited literature on maternal characteristics associated with poor compliance with prenatal syphilis testing. Studies have shown that lack or late initiation of prenatal care, [4][5][6][7][8] single marital status, 5 tobacco, alcohol or drug use, 4,5,8 and rural residence 4 are associated with congenital syphilis infections and may represent factors associated with barriers to prenatal screening. In 2007, a syphilis outbreak was declared in the Canadian province of Alberta.…”
mentioning
confidence: 99%